Reception of Sophocles’ Antigone in the Baltic States - Lotman, Maria-Kristiina; Bodniece, Līva; Dikmonienė, Jovita (Literatūra, 2022)
This paper analyzes the translations of Antigone by Sophocles and later authors and the performances based on them in the theaters of Estonia, Latvia and Lithuania. It investigates the necessity to translate the Antigone dramas by Sophocles, Jean Anouilh and Janusz Głowacki into national languages and stage them in theaters. The article analyzes how these works are related to the history of the Baltic countries. This paper is divided into three subparts that match the historical periods from the end of the nineteenth century to the beginning of the twenty-first century. The most important performances of Antigone in the Baltic countries are analyzed, highlighting the individual style of each director and their attention to the form and expression of the performances. The main themes revealed by the artists of the Baltic countries are conscious self-sacrifice for one’s neighbor and individual resistance to conformity and tyranny.
Keywords: Antigone; Sophocles; Anouilh; Głowacki; drama; theater; performance